2019
DOI: 10.14338/ijpt-18-00041.1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Spacer Reduces Rectal Dose during Proton Therapy for Prostate Cancer: A Dosimetric Analysis

Abstract: Purpose: Proton therapy for prostate cancer may reduce bowel dose and risk of bowel symptoms relative to photon-based methods. Here, we determined the effect of using a biodegradable, injectable hydrogel spacer on rectal dose on plans for treating prostate cancer with intensity-modulated proton therapy (IMPT) or passive scattering proton therapy (PSPT). Materials and Methods: Pairs of IMPT and PSPT plans for 9 patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…As a result, we confirmed that rectal dose was significantly reduced in the HS-inserted group compared with the non-inserted group as in a previous report [ 13 ]. In addition, both groups showed a significant correlation with changes in rectal volume in the AP prostate displacement, but the absolute amount tended to be smaller in the HS-inserted group.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, we confirmed that rectal dose was significantly reduced in the HS-inserted group compared with the non-inserted group as in a previous report [ 13 ]. In addition, both groups showed a significant correlation with changes in rectal volume in the AP prostate displacement, but the absolute amount tended to be smaller in the HS-inserted group.…”
Section: Discussionsupporting
confidence: 91%
“…The use of hydrogel rectal spacers for proton prostate treatment is considered to be effective to reduce the rectal dose, resulting in lower toxicity by making space between the rectum and prostate. The use of this technique can be expected to increase, but the stability of implantation as well as the absorption rate of a biodegradable compound over the treatment period must be studied by using several imaging modalities to adjust treatment plans appropriately 14,15 . In particular, the implantation stability around the SV region is questionable, since the daily movement of the rectum around this region was found to be significant herein.…”
Section: Discussionmentioning
confidence: 99%
“…The use of this technique can be expected to increase, but the stability of implantation as well as the absorption rate of a biodegradable compound over the treatment period must be studied by using several imaging modalities to adjust treatment plans appropriately. 14,15 In particular, the implantation stability around the SV F I G . 8.…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective multi-institutional studies 10 , 11 and a number of retrospective clinical or dosimetric studies have demonstrated the feasibility of rectal spacer application with improvement in rectal sparing. 13 , 14 , 15 , 16 , 29 , 30 , 31 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Several prospective multi-institutional studies [10,11] as well as a number of retrospective clinical or dosimetric studies have demonstrated the feasibility of rectal spacer application with improvement in rectal sparing. [13][14][15][16][29][30][31][32][33] Song et al [10] reported the results of a multi-institutional study where hydrogel resulted in > 7.5-mm prostate-rectal separation in 95.8% of patients with 95.7% achieving a reduction in rV70 of > 25%. Eligibility was limited to prostate glands < 80 cc.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%